2003
DOI: 10.1046/j.1471-4159.2003.02132.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cln3p, the gene product responsible for juvenile neuronal ceroid lipofuscinosis, as a lysosomal integral membrane glycoprotein

Abstract: Juvenile neuronal ceroid lipofuscinosis (JNCL) is an autosomal recessively inherited lysosomal storage disease involving a mutation in the CLN3 gene. The sequence of CLN3 was determined in 1995; however, the localization of the CLN3 gene product (Cln3p) was not confirmed. In this study, we investigated endogenous Cln3p using two peptide antibodies raised against two distinct epitopes of murine Cln3p. Identification of the liver 60 kDa protein as Cln3p was ascertained by amino acid sequence analysis using tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 52 publications
1
65
0
Order By: Relevance
“…In non-neuronal cells, CLN3 localizes primarily to endosomes and lysosomes (Haskell et al, 2000;Ezaki et al, 2003;Mao et al, 2003;Kyttala et al, 2004), whereas in neurons, CLN3 is also detected in vesicular structures at synapses and along neurites (Haskell et al, 2000;Luiro et al, 2001;Kyttala et al, 2004). These findings suggest that in most/all cell types, CLN3 performs a basic function related to the lysosome, whereas in neurons, CLN3 may take on additional specialized tasks.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In non-neuronal cells, CLN3 localizes primarily to endosomes and lysosomes (Haskell et al, 2000;Ezaki et al, 2003;Mao et al, 2003;Kyttala et al, 2004), whereas in neurons, CLN3 is also detected in vesicular structures at synapses and along neurites (Haskell et al, 2000;Luiro et al, 2001;Kyttala et al, 2004). These findings suggest that in most/all cell types, CLN3 performs a basic function related to the lysosome, whereas in neurons, CLN3 may take on additional specialized tasks.…”
Section: Introductionmentioning
confidence: 94%
“…In adult murine brain, immunostaining and/or in situ hybridization for transcript localizes CLN3 to neurons in the cortex, hippocampus, cerebellum, thalamus, and hypothalamus (Luiro et al, 2001;Cotman et al, 2002). Immunoblot of lysates from murine tissues shows abundant CLN3 in liver, kidney, and spleen and low amounts in pancreas and brain (Ezaki et al, 2003). A study on human tissues showed low CLN3 levels in the liver but high levels in brain by immunoblot of tissue lysates (Margraf et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…To first determine whether the CLN3-encoded protein, battenin, was present in the different AV fractions, which might suggest a direct role for battenin in the autophagic pathway, we probed immunoblots of wild-type (Cln3 ϩ/ϩ ) and homozygous Cln3 ⌬ex7/8 fractions using a previously characterized anti-battenin antibody (23). On wild-type immunoblots, we observed a faint ϳ60 -65-kDa smear (asterisk in Fig.…”
Section: Battenin Is Highly Enriched In Purified Autophagic Vacuoles-mentioning
confidence: 99%
“…PPT1 and TPP1 are both proteins with known lysosomal functions. Battenin, the gene product of CLN3, although its function is unknown, has been demonstrated to localize to the lysosomal membrane (Ezaki et al 2003).…”
mentioning
confidence: 99%